Islamic mortgage adoption: examining the moderating effects of Islamic altruism - Khadijah M. Sayuti; Hanudin Amin (Emerald Group Publishing Limited, 2021)
Purpose – Using the theory of planned behaviour (TPB) as an analytical framework, this paper aims to investigate the direct effects of attitude, subjective norm, perceived behavioural control, price fairness and Islamic altruism. It also explores how these path linkages can be moderated by Islamic altruism. Design/methodology/approach – Data are gathered via survey questionnaires on 287 Muslim bank customers in major cities of East Malaysia. The data are then tested using partial least squares. Findings – The results show that attitude, subjective norm, perceived behavioural control, price fairness and Islamic altruism are significantly influenced by Muslim bank customers’ intention to choose Islamic home financing products. Islamic altruism is also found to significantly moderate the relationship between price fairness and behavioural intention. Research limitations/implications – Three limitations are available for future research that include the geographical restriction, respondents’ selection and a limited number of battery items used. Practical implications – Essentially, the results of this study serve as a guide for Islamic bank managers or mortgage providers to improve their pertinent marketing strategies, which are vital to enhancing the acceptance rate of Islamic mortgage. Originality/value – This study extends the TPB model by incorporating price fairness and Islamic altruism into the Islamic home financing context. Keywords Consumer Behavior, Price fairness, Theory of planned behaviour (TPB), Islamic home financing, Islamic altruism.